Portfolio Diversification and Oil Price Shocks: A Sector Wide Analysis - Ali, Mohsin; Azmi, Wajahat; Khan, Aftab Parvez (International Journal of Energy Economics and Policy, 2019)
This paper investigates the time-varying relationship between the oil price and disaggregated stock market of India using Dynamic conditional correlation multivariate GARCH and Continuous Wavelet Transformation modelling approaches. Our findings reveal the evolving relationship between the oil price and disaggregated stock market. The correlations are generally volatile before the 2007-08 crisis but since then the correlations are positive implying no diversification benefits for the investors during rising oil prices. As emerging markets in general, and India in particular, is expected to increase its share of oil consumption in the world’s energy market, therefore for the stock market to grow, especially the oil-intensive industries, we recommend the government should increase its reliance on alternative energy resources. Furthermore, as rising oil prices can also have its adverse effect through exchange rate channel, we suggest the monetary policies should be time varying to manage the oil inflationary pressures arising out of extreme volatility in the oil prices. Keywords: DCC-GARCH, CWT, Disaggregated stock market, India, Oil price shocks, Diversification. JEL Classifications: C50; G10; O53; Q43 DOI: https://doi.org/10.32479/ijeep.7747